Immunization with 10-valent pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) according to different schedules in infants in South Africa: a phase III trial. (3rd June 2017) - Madhi, Shabir A; Koen, Anthonet; Jose, Lisa; Moreira, Marta; van Niekerk, Nadia; Cutland, Clare; François, Nancy; Ruiz-Guiñazú, Javier; Yarzabal, Juan Pablo; Borys, Dorota; Schuerman, Lode
ABSTRACT: Background : Limited clinical data exists to assess differences between various infant pneumococcal conjugate vaccine schedules. In this trial, we evaluated immunogenicity of the 10-valent pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) administered using 3 different immunization schedules in HIV unexposed-uninfected infants in South Africa. Methods : In this phase III, open, single‐center, controlled study (clinicaltrials.gov: NCT00829010), 300 infants were randomized (1:1:1) to 1 of 3 PHiD-CV schedules: 3-dose priming and booster (3 + 1); 3-dose priming without booster (3 + 0); or 2-dose priming and booster (2 + 1). The booster was administered at 9–10 months of age. immune responses were assessed up to 21 months after primary vaccination. Results : Post‐priming antibody levels tended to be lower in the 2 + 1 group. At 6 months post‐priming, antibody concentrations and opsonophagocytic activity titers were within similar ranges after 2‐ or 3‐dose priming. Robust increases were observed pre‐ to post‐booster in the 3 + 1 and 2 + 1 groups. Conclusions : PHiD-CV was immunogenic when administered in different schedules. Post‐booster responses suggest effective immunological priming with both 2‐ and 3‐dose primary series and support administration of the booster dose at 9–10 months of age.